How about “Shifting Tides: The Evolving Landscape of Consumer Choices - Lili Suryati (Greenation International Journal of Tourism and Management, 2023)
The purpose of this study was to determine the reasons or factors that encourage consumers to decide to buy hotel rooms at The Luxton Bandung. The research conducted is explanatory research, namely research that aims to analyze the relationships between one variable and another or how one variable affects another. Data collection methods using questionnaires and interviews. From the results of data analysis, it is known that the factors that influence consumers to stay at The Luxton Bandung Hotel consist of price, promotion, speed in providing confirmation of room reservations, ease of access to room reservations and payment methods.